Gold Nanoparticle-Enhanced Molecularly Imprinted Polymer Electrode for Non-Enzymatic Lactate Sensing - Christopher Animashaun; Abdellatif Ait Lahcen; Gymama Slaughter (Biosensors, 2025)
We are reporting the development of a high-performance, non-enzymatic electrochemical biosensor for selective lactate detection, integrating laser-induced graphene (LIG), gold nanoparticles (AuNPs), and a molecularly imprinted polymer (MIP) synthesized from poly(3,4-ethylenedioxythiophene) (PEDOT). The LIG electrode offers a highly porous, conductive scaffold, while electrodeposited AuNPs enhance catalytic activity and signal amplification. The PEDOT-based MIP layer, electropolymerized via cyclic voltammetry, imparts molecular specificity by creating lactate-specific binding sites. Cyclic voltammetry confirmed successful molecular imprinting and enhanced interfacial electron transfer. The resulting LIG/AuNPs/MIP biosensor demonstrated a wide linear detection range from 0.1 µM to 2500 µM, with a sensitivity of 22.42 µA/log(µM) and a low limit of detection (0.035 µM). The sensor showed excellent selectivity against common electroactive interferents such as glucose and uric acid, long-term stability, and accurate recovery in artificial saliva (>95.7%), indicating strong potential for practical application. This enzyme-free platform offers a robust and scalable strategy for continuous lactate monitoring, particularly suited for wearable devices in sports performance monitoring and critical care diagnostics.